2019
DOI: 10.1038/s41598-019-47161-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and patterns of tuna spawning inside a large no-take Marine Protected Area

Abstract: The Phoenix Islands Protected Area (PIPA), one of the world’s largest marine protected areas, represents 11% of the exclusive economic zone of the Republic of Kiribati, which earns much of its GDP by selling tuna fishing licenses to foreign nations. We have determined that PIPA is a spawning area for skipjack ( Katsuwonus pelamis ), bigeye ( Thunnus obesus ), and yellowfin ( Thunnus albacares ) tunas. Our approach included sampling larvae on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…While empirical studies have demonstrated spillover benefits for some species (13,15,16,21,50,(57)(58)(59) and provide support for fisheries benefits of both small (57-59) and large (39)(40)(41) MPAs, the majority of the species considered in our analyses lack empirical support (one way or the other) for spillover effects. Furthermore, while we rely only on MPA size as an important aspect of reserve design (25, 60-62), we recognize that other factors, such as MPA geometry, spacing, age, and habitat quality, also affect spillover (14,(63)(64)(65).…”
Section: Significancementioning
confidence: 58%
See 1 more Smart Citation
“…While empirical studies have demonstrated spillover benefits for some species (13,15,16,21,50,(57)(58)(59) and provide support for fisheries benefits of both small (57-59) and large (39)(40)(41) MPAs, the majority of the species considered in our analyses lack empirical support (one way or the other) for spillover effects. Furthermore, while we rely only on MPA size as an important aspect of reserve design (25, 60-62), we recognize that other factors, such as MPA geometry, spacing, age, and habitat quality, also affect spillover (14,(63)(64)(65).…”
Section: Significancementioning
confidence: 58%
“…Furthermore, while unaccounted for in our current model, large and remote MPAs may protect ecologically important areas that are vital for certain life history stages of even highly migratory species, which may result in fisheries benefits for target stocks. For example, tuna spawn inside the Phoenix Island Protected Area (39), and there is an increasing body of evidence demonstrating potential fisheries benefits from MPAs for pelagic populations in the Chagos Archipelago (40) and the Galápagos Marine Reserve (41).…”
Section: Significancementioning
confidence: 99%
“…The contrasting movement patterns exhibited by different yellowfin life stages and studies conducted over a decade apart have demonstrated that tuna movement between tropical and temperate regions remains inadequately understood (Holland et al, 1999;Pecoraro et al, 2017Pecoraro et al, , 2018Anderson et al, 2019). As the Central North Pacific faces various anthropogenic stressors (Erauskin-Extramiana et al, 2019;Woodworth-Jefcoats et al, 2019) and stakeholders experience potential changes to fisheries management and conservation measures such as creation of large-scale marine protected areas (Richardson et al, 2018;Hernández et al, 2019), availability of yellowfin tuna and economic impacts to local communities will remain a serious issue.…”
Section: Discussionmentioning
confidence: 99%
“…While there is limited understanding of spawning behaviors of most pelagic species [ 80 ], bigeye, yellowfin, skipjack and albacore tunas are currently understood to have extensive spawning grounds in tropical and subtropical waters and protracted spawning seasons [ 79 , 81 ]. While tuna spawning habitat very likely occurs within the monument components assessed here and other pelagic MPAs of the tropical Pacific [ 82 ], for these highly fecund broadcast spawners, protecting a small proportion of the distribution of spawning stock biomass likely has minimal effect on recruitment or absolute biomass, where only at extremely low population sizes would egg production likely be a limiting factor for recruitment [ 83 , 84 ]. If individuals are transient, remaining for relatively short time periods (days, weeks) in an MPA, especially if fishing-the-line occurs, then there would not be an increase in biomass from the MPA, locally or stock-wide [ 11 , 20 , 85 86 ].…”
Section: Discussionmentioning
confidence: 99%